Redwood court : fiction - Dameron, DéLana R. A. (Reese's book club., 2024)
"'Mika, you sit at our feet all these hours and days, hearing us tell our tales. You have all these stories inside you: all the stories everyone in our family knows and all the stories everyone in our family tells. You write 'em in your books and show everyone who we are.' So begins DéLana R.A. Dameron's stunning novel-in-stories, Redwood Court. The baby of the family, Mika Mosby spends much of her time in the care of loved ones, listening to their stories and secrets, witnessing their struggles. Growing up on Redwood Court, the cul-de-sac in the working-class suburb of Columbia, South Carolina where her grandparents live, Mika learns important, sometimes difficult lessons from the people who raise her: Her exhausted parents, who work long hours at multiple jobs while still making sure their kids experience the adventure of family vacations; her older sister, who, in a house filled with Motown would rather listen to Alanis Morrisette, and can't wait to taste real independence; her retired grandparents, children of Jim Crow, who realized their own vision of success when they bought their house on Redwood Court in the 1960s, imagining it filled with future generations; and the many neighbors on the Court who hold tight to the community they've built, committed to fostering joy and love in an America so insistent on seeing Black people stumble and fall"--